Erythropoietin Receptor Signaling through STAT3 Is Required for Glioma Stem Cell Maintenance - Cao, Yiting (SAGE Publications, 2010)
Recombinant erythropoietin (EPO) is a growth factor used in the treatment of chemotherapy-induced anemia, but recent studies suggest that EPO may accelerate cancer growth. Although several cancers express EPO receptors (EPORs), the mechanism by which EPOR promotes tumor growth remains poorly understood. Glioblastomas display a cellular hierarchy of self-renewal and tumor propagation restricted to glioma stem cells (GSCs). The authors find that GSCs express higher levels of EPOR than matched nonstem glioma cells. Prospective enrichment for EPOR on GSCs increased neurosphere formation, suggesting that EPOR can select for a subset of GSCs with increased self-renewal capacity. Targeting EPOR expression with lentiviral-mediated short-hairpin RNA (shRNA) reduced GSC growth, survival, and neurosphere formation capacity, defining a crucial role for EPOR in GSC maintenance. The authors further find that STAT3 is an important mediator of EPOR signals in GSCs. EPOR knockdown attenuated the basal activation of STAT3 present in GSCs, and a small-molecule inhibitor of STAT3 reduced GSC growth and survival. EPOR signaling was critical for survival in vivo, as targeting EPOR expression decreased GSC tumorigenic potential. Elevated EPOR expression is also associated with poor patient outcome. Thus, EPOR on GSCs promotes tumor growth and may explain the poor survival of cancer patients treated with EPO.